Novel Immune-Based treatments for Diffuse Large B-Cell Lymphoma: The Post-CAR T Cell Era - Atallah-Yunes, Suheil Albert; Robertson, Michael J.; Davé, Utpal P.; Ghione, Paola; Perna, Fabiana (Frontiers in Immunology, 2022)
Prognosis for patients with refractory/relapsed (R/R) diffuse large B-cell lymphoma (DLBCL) is poor. Immune-based therapeutic treatments such as CD19 Chimeric antigen receptor (CAR) T-cell therapies have dramatically changed the treatment landscape for R/R DBCL leading to durable remissions in ~ 50% of patients. However, there remains an unmet need for developing novel therapies to improve clinical outcomes of patients not responding or relapsing after CAR T-cell therapies. Lack of suitable immunotherapeutic targets and disease heterogeneity represent the foremost challenges in this emerging field. In this review, we discuss the recently approved and emerging novel immunotherapies for patients with R/R DLBCL in the post-CAR T era and the cell surface targets currently used.